2022
DOI: 10.3389/fimmu.2022.1046778
|View full text |Cite
|
Sign up to set email alerts
|

Increased formation of neutrophil extracellular traps in patients with anti-N-methyl-d-aspartate receptor encephalitis

Abstract: BackgroundNeutrophil extracellular traps (NETs) have been found to play an important role in several nervous system diseases. However, their role in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis remains unclear. The purpose of this study was to examine the possible role of NETs in anti-NMDAR encephalitis.Materials and methodsEleven patients with anti-NMDAR encephalitis and ten healthy participants were enrolled. Plasma NETs levels were detected using an immunofluorescence assay and enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
(52 reference statements)
0
8
0
1
Order By: Relevance
“…Saf. 207, 111081. doi: 10.1016/j.ecoenv.2020 Nie, K., Bai, Q., Chen, C., Zhang, M., and Li, Y. (2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Saf. 207, 111081. doi: 10.1016/j.ecoenv.2020 Nie, K., Bai, Q., Chen, C., Zhang, M., and Li, Y. (2022).…”
Section: Discussionunclassified
“…In addition, Elrys et al (2020) reported that under salt stress FA could promote the growth of wheat by reducing the level of active oxygen species and improving the antioxidant defense system. Potassium fulvic acid (PFA) is formed with FA by chelating K + and rich in exchangeable K (Qiao et al, 2022). Compared with FA, PFA has superior advantages in composition, performance, price and physiological activity Qiao et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils may contribute to the pathology of CNS diseases by generating NETs. In a recent study on patients with anti-NMDAR encephalitis, the production of NET increased, and the NET levels were found to be correlated with the levels of IL-8, IL-6, and TNF-α ( 21 ). Neutrophils may enhance immune response via NET generation in AE pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tumorigenesis, NETs facilitate cancer metastasis by forming circulating tumor cell clusters, enhancing tumor cell adhesion to the endothelium and potentially increasing tumor cell extravasation 8,9 . Citrullinated histone H3 (H3Cit) is a central player in NET formation 10,11 . NETs have been reported to be involved in CRC development and metastasis 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Citrullinated histone H3 (H3Cit) is a central player in NET formation. 10,11 NETs have been reported to be involved in CRC development and metastasis. 12,13 Peptidyl arginine deiminase (PAD) enzymes are widely distributed in mammals and are closely related to cell development and differentiation.…”
mentioning
confidence: 99%